Influence of time and gender on the level of electronic transparency of Peruvian public universities in Metropolitan Lima - Chuco-Sullca, Gina (2021)
This work presents a quantitative, cross-sectional, non-experimental and correlational investigation on the evaluation of the level of electronic transparency in the public universities of Metropolitan Lima. The objective was to determine the level of electronic transparency and its relationship with the years of existence of each university and the gender of its representatives, under the framework of the Transparency Law, for which 6 public universities that complied with the portal were evaluated. of transparency. Content and form indicators were developed, adapted from the Guidelines for the Implementation of the Standard Transparency Portal in Public Administration Entities. The analysis closes the evaluation in the fourth quarter of 2020.